Analysis of waveguide polarizers using equivalent network and finite elements methods - Piltyay, S. I.; Bulashenko, A. V.; Kalinichenko, Ye. I. (Journal of electromagnetic waves and applications, 2022)
Current research is dedicated to the development of new theoretical model for guide polarization converter with irises. New created model is derived based on the equivalent circuits and transmission line representations. Specific feature of the model consists in the possibility of account of irises thickness in the simulations by approximate single-mode method. Using equivalent lumped elements of the circuits we obtained general scattering matrices of the polarization transformer for fundamental modes of vertical and horizontal linear polarizations. Besides, numerical simulations and optimization of the device were carried out by finite elements method. Good agreement of obtained optimal sizes and polarization characteristics is observed. Provided by the polarizer phase difference between two orthogonal polarizations falls within range 90°±5° in the operating Ku-band. Calculated ellipticity coefficient is better than 1.5 dB. Developed model can be applied for designing of new waveguide polarization converters, filters and other waveguide components with irises.